dada a função f(x) = 2x^2-3x-1, o valor de f (0)+4.f(2)-f(-1) é:
Soluções para a tarefa
Respondido por
2
F(0) + 4F(2) - F (-1) =
(2.(0)² -3(0) - 1) + 4.[2.(2)² - 3(2) - 1] - [ 2(-1)² - 3(-1) - 1] =
( -1) + 4(1) - (4) = -1
Bons estudos, abraços!
(2.(0)² -3(0) - 1) + 4.[2.(2)² - 3(2) - 1] - [ 2(-1)² - 3(-1) - 1] =
( -1) + 4(1) - (4) = -1
Bons estudos, abraços!
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Química,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás